Inhibition of longevity regulator PAPP‐A modulates tissue homeostasis via restraint of mesenchymal stromal cells. Issue 3 (9th February 2021) - Mohrin, Mary; Liu, Justin; Zavala‐Solorio, Jose; Bhargava, Sakshi; Maxwell Trumble, John; Brito, Alyssa; Hu, Dorothy; Brooks, Daniel; Koukos, Georgios; Alabdulaaly, Lama; Paw, Jonathan S.; Hake, Kayley; et al.
Abstract: Pregnancy‐associated plasma protein‐A (PAPP‐A) is a secreted metalloprotease that increases insulin‐like growth factor (IGF) availability by cleaving IGF‐binding proteins. Reduced IGF signaling extends longevity in multiple species, and consistent with this, PAPP‐A deletion extends lifespan and healthspan; however, the mechanism remains unclear. To clarify PAPP‐A's role, we developed a PAPP‐A neutralizing antibody and treated adult mice with it. Transcriptomic profiling across tissues showed that anti‐PAPP‐A reduced IGF signaling and extracellular matrix (ECM) gene expression system wide. The greatest reduction in IGF signaling occurred in the bone marrow, where we found reduced bone, marrow adiposity, and myelopoiesis. These diverse effects led us to search for unifying mechanisms. We identified mesenchymal stromal cells (MSCs) as the source of PAPP‐A in bone marrow and primary responders to PAPP‐A inhibition. Mice treated with anti‐PAPP‐A had reduced IGF signaling in MSCs and dramatically decreased MSC number. As MSCs are (1) a major source of ECM and the progenitors of ECM‐producing fibroblasts, (2) the originating source of adult bone, (3) regulators of marrow adiposity, and (4) an essential component of the hematopoietic niche, our data suggest that PAPP‐A modulates bone marrow homeostasis by potentiating the number and activity of MSCs. We found that MSC‐like cells are the major source of PAPP‐A in other tissues also, suggesting that reduced MSC‐like cell activity drives the system‐wide reduction in ECM gene expression due to PAPP‐A inhibition. Dysregulated ECM production is associated with aging and drives age‐related diseases, and thus, this may be a mechanism by which PAPP‐A deficiency enhances longevity. Abstract : Deletion of pregnancy‐associated plasma protein‐A (PAPP‐A) extends lifespan and healthspan. To understand why, we studied pharmacological inhibition of PAPP‐A in adult mice. PAPP‐A inhibition reduced IGF signaling and extracellular matrix gene expression system wide. We found that PAPP‐A is produced by mesenchymal stromal cells and is required for their persistence in vivo. PAPP‐A inhibition reduced MSC number, leading altered bone marrow homeostasis: reduced bone, adiposity, and myelopoiesis.